Impact of climate smart technoloies on crop yield and livilihood of the farmers in the state Karnataka - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
A consortium of CGIAR institutions led by ICRISAT conducted demonstrations of improved technologies including climate smart technologies (DSR, Zero Tillage, LLL, Soil Nutrient Managment) in the farmers' fields in 4 selected districts in Karnataka since 2015. IFPRI conducted various rounds of primary surveys to assess the impact of the above mentioned technologies on crop yields, farmers' income and building resilience (against drought).